Risk Management and Organizational Resilience: Analysis of the Italian Scenario During Covid-19 Pandemic, with A Look at the Challenges of Technology and Sustainability - Renzetti Cristina; Mango Lucio (Journal of Big Data Research, 2020)
The Coronavirus emergency represents an epochal challenge for all world health organizations. In these times of profound destabilization of healthcare organizations, become urgent some thoughts on how to deal with the organization and re-engineering process as well as on concepts, relatively new, such as
Keywords: Covid-19